Germline ERBB3 mutation in familial non-small-cell lung carcinoma: expanding ErbB's role in oncogenesis. Issue 24 (19th July 2021) - McInerney-Leo, Aideen M; Chew, Hui Yi; Inglis, Po-Ling; Leo, Paul J; Joseph, Shannon R; Cooper, Caroline L; Okano, Satomi; Hassall, Tim; Anderson, Lisa K; Bowman, Rayleen V; Gattas, Michael; Harris, Jessica E; et al.
Abstract: Lung cancer is the commonest cause of cancer deaths worldwide. Although strongly associated with smoking, predisposition to lung cancer is also heritable, with multiple common risk variants identified. Rarely, dominantly inherited non-small-cell lung cancer (NSCLC) has been reported due to somatic mutations in EGFR/ErbB1 and ERBB2 . Germline exome sequencing was performed in a multi-generation family with autosomal dominant NSCLC, including an affected child. Tumour samples were also sequenced. Full-length wild-type (wtErbB3) and mutant ERBB3 (mutErbB3) constructs were transfected into HeLa cells. Protein expression, stability, and subcellular localization were assessed, and cellular proliferation, pAkt/Akt and pERK levels determined. A novel germline variant in ERBB3 (c.1946 T > G: p.Iso649Arg), coding for receptor tyrosine-protein kinase erbB-3 (ErbB3), was identified, with appropriate segregation. There was no loss-of-heterozygosity in tumour samples. Both wtErbB3 and mutErbB3 were stably expressed. MutErbB3-transfected cells demonstrated an increased ratio of the 80 kDa form (which enhances proliferation) compared with the full-length (180 kDa) form. MutErbB3 and wtErbB3 had similar punctate cytoplasmic localization pre- and post-epidermal growth factor stimulation; however, epidermal growth factor receptor (EGFR) levels decreased faster post-stimulation in mutErbB3-transfected cells, suggesting more rapid processing of the mutErbB3/EGFR heterodimer. Cellular proliferation was increased in mutErbB3-transfected cells compared with wtErbB3 transfection. MutErbB3-transfected cells also showed decreased pAkt/tAkt ratios and increased pERK/tERK 30 min post-stimulation compared with wtErbB3 transfection, demonstrating altered signalling pathway activation. Cumulatively, these results support this mutation as tumorogenic. This is the first reported family with a germline ERBB3 mutation causing heritable NSCLC, furthering understanding of the ErbB family pathway in oncogenesis.